The Development of Batak and Malay Batik Motif Stilation in Improving the Creative Industry in Indonesia - Farihah Farihah; Dina Ampera; Halimul Bahri; Yudhistira Anggraini; Bakhrul Khair Amal (Randwick International of Social Science Journal, 2021)
The purpose of this study was to determine the stylization of Batak and Malay batik motifs by developing the shape of a typical Batak batik motif with a typical Malay batik motif and to determine the process of developing a Batak and Malay batik motif design. The target of the research is to create and produce designs of stylized Batak and Malay batik motifs and to conduct batik trials on fabrics with motifs that have been developed, so as to produce textile products in the form of a blend of batik cloth between two tribes in North Sumatra. The research method used is the development research method (R&D). The research model is the IDI (instructional, development, Institute) development model, which includes three stages: define, develop, evaluate. The define stage includes: identifying problems, needs analysis, motive characteristic analysis, design concept analysis. The develop stage includes: development of motif designs and validation of product results by experts (validators). The results showed that Batak and Malay batik products deserve to be developed as a creative industry. The first validation gave a score of 0.89, the second validation got a score of 0.86 and the third validation obtained a score of 0.94. The average value of the validation results is 0.89, so the results of research on the development of stylized Batak and Malay batik motifs are included in the appropriate category and can improve the creative industry in Indonesian.